ANALYSIS AND EVALUATION OF DEVELOPMENT OF INTELLECTUAL POTENTIAL OF HUMAN RESOURCES OF UKRAINE (Regional aspects of productive forces development of Ukraine, 2024)
Introduction. The development of the intellectual potential of human resources of Ukraine at the current stage as an important factor that allows an effective use of national resources and ensures the prosperity of the country in general have been studied.Goal. To research on development of the intellectual potential of human resources of Ukraine. To achieve this goal, the following tasks have been formulated: to investigate the essence of development of the intellectual potential of human resources; analyze and evaluate the current state of the intellectual potential of human resources in Ukraine; formulate the key aspects of development of the intellectual potential of the country’s human resources.Research methods. Methods of statistical, systematic, structural analysis and generalization were used.The results. The essence and significance of development of the intellectual potential of human resources have been studied, the state of the intellectual potential of human resources in Ukraine has been analyzed and assessed, and a study of the scientific and innovative capacity of the Ukrainian economy has been carried out according to the indicators of world ratings. The results of our research showed the scientific and innovative industries, which are important elements of the future of the national economy, are currently experiencing difficult times in Ukraine due to lack of funding, loss of talented people, high risks, lack of public attention etc. Other factors influence this sphere, the most serious of which is Russia's military aggression against Ukraine.The position of Ukraine in the international ranking of innovative development indicates the presence of a high level of scientific and educational potential, which is the basis of the competitiveness of the scientific and innovative spheres of Ukraine and is the basis for development and innovation, new equipment and technologies. However, according to the results of our assessment of the scientific and innovative potential of Ukraine, a number of problems were identified: the presence of ineffective and weak mechanisms for implementation and further commercialization of innovations in the field of economic activity; insufficient level of support and financing of innovative projects; low level of cooperation between innovative companies and scientific institutions. The results of assessment of the scientific and innovative potential of Ukraine indicate the need to develop and implement a unified and coordinated scientific, technological and innovative policy. It indicates the need for serious steps towards the necessary structural changes in the economy and science, technological modernization of production and promotion of innovations in business. The key aspects of development of the intellectual potential of the country’s human resources are formulated.Conclusions. The main provisions of the scientific article will contribute to the effective development of the intellectual potential of Ukraine's human resources.